2022
DOI: 10.1055/a-1883-1021
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Disorders of Consciousness: Past, Present, and Future

Abstract: With the advent of advanced analytical methods applied to functional neuroimaging and neurophysiological data, cerebral conditions have been defined that challenge the established classification of disorders of consciousness. A subset of brain-damaged patients has been identified who cannot carry out motor commands, but who exhibit patterns of cerebral activation during mental imagery tasks that are indistinguishable from those in healthy controls. This condition, termed "cognitive motor dissociation", has ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 106 publications
0
5
0
2
Order By: Relevance
“…Состояние минимального сознания (СМС) -это клиническое состояние, сопровождающееся тяжелым нарушением сознания, при котором тем не менее имеют место отчетливые, хотя и минимальные, часто нес тойкие признаки целенаправленного поведения, свидетельствующие об осознании пациентом собственной личности или окружаю щей действительности [1,2,4].…”
Section: рефератunclassified
See 1 more Smart Citation
“…Состояние минимального сознания (СМС) -это клиническое состояние, сопровождающееся тяжелым нарушением сознания, при котором тем не менее имеют место отчетливые, хотя и минимальные, часто нес тойкие признаки целенаправленного поведения, свидетельствующие об осознании пациентом собственной личности или окружаю щей действительности [1,2,4].…”
Section: рефератunclassified
“…Выход из СМС [1,2] -это состояние, которое формируется по мере восстановления когнитивных функций, когда пациент отчетливо демонстрирует функционально значимое поведение, т. е. способен выполнять действия, позволяющие ему достаточно эффективно взаимодействовать с окружающим миром. Функционально значимое поведение включает в себя функциональную коммуникацию, которая может осуществляться с помощью устной или письменной речи, условных знаков, означающих «да» и «нет», или специальных устройств для облегчения общения, и целенаправленное (функциональное) использование предметов, т. е. наличие у пациента возможности отличать один предмет от другого и применять их в соответствии с их предназначением.…”
Section: рефератunclassified
“…The terminology describing the various types of covert brain activity fueling this transformation is shifting the definitions of DoC from pure behavior-based definitions to those incorporating the detectable brain states by advanced methods ( Table 1 ). 23 The utilization of newer terms may increase due to their potential to classify the highest DoC–brain state above that of behaviors seen on exam 34 and increase accuracy of outcome prediction. 1 Even more importantly, the detection of brain activity indicating potential for good outcome may lead to the development of targeted therapies, such as pharmacologic agents, brain stimulation, and brain–computer interfaces.…”
Section: Advanced Doc Terminology: Shift To Brain-state–based Paradig...mentioning
confidence: 99%
“…However, it has been found that passive paradigms have a greater likelihood of capturing preserved consciousness ( Kondziella et al, 2016 ; Aubinet et al, 2022 ). The scientific understanding of CMD is evolving, but current evidence suggests it is likely a distinct phenomenon separate from the DoC spectrum ( Kondziella and Stevens, 2022 ), more akin to a functionally locked-in syndrome. Evidence suggests those who are identified as CMD while in the ICU have an improved functional recovery as compared to those unresponsive patients who demonstrate no evidence of consciousness with advanced neuroimaging ( Edlow et al, 2017 , 2021 ).…”
Section: Neurobehavioral Assessment Across Care Settings: Impact Of C...mentioning
confidence: 99%